Cognitive functioning in Williams syndrome: a study in Portuguese and Spanish patients - Sampaio, Adriana (2009)
Williams Syndrome (WS) is a genetic neurodevelopmental disorder caused by a submicroscopic deletion on chromosome 7 q11.23. This is a systemic disorder in which cardiac problems and mental retardation are the key phenotypic symptoms. Although displaying a general cognitive impairment, they are most often described as exhibiting a peak and valley profile, with relative sparing of language and face processing abilities and severe impairment of visual–spatial cognition. In this study, we conducted a detailed cognitive assessment using Wechsler Intelligence Scales on a WS and a normal development control group. To explore the hypothesis of a dissociative cognitive architecture in WS, performance on subtests, factorial indexes and composite measures of Verbal, Performance and Full Scale Intelligence Quotient were analysed. Individuals with WS were found to score in Full Scale Intelligence Quotient (FSIQ) within mild to moderate mental retardation interval, and had significantly lower scores in all measures when they were compared with the normal development group. However, a specific intragroup cognitive profile was found for Williams Syndrome (confirming Mervis’ definition of the WS cognitive profile) along with a specific developmental pathway (absence of an age-associated cognitive decline).